1950
DOI: 10.1111/j.1467-6494.1950.tb01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Individual's Reactions to Color in Ink Blots

Abstract: In a previous expenment we investigated the mfluence of color on reactions to ink blots by a technique in which two independent groups of subjects were presented matched chromatic and achromatic blots (3) This technique was used to demonstrate that when the color vanable is completely isolated it has measurable effects which show up as group differences or trends in both the reaction time and the content of the conceptual responses But such a technique employing mdependent groups for chromatic and achromatic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1955
1955
1963
1963

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Eleven of the 13 blots used were details taken from the standard Rorschach blots. Of these, nine were used by Siipola (1950). The blots, their source, and data concerning associated responses appear in Wiener (1954, Appendix B).…”
Section: Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven of the 13 blots used were details taken from the standard Rorschach blots. Of these, nine were used by Siipola (1950). The blots, their source, and data concerning associated responses appear in Wiener (1954, Appendix B).…”
Section: Tasksmentioning
confidence: 99%
“…This prediction was tested on a motor learning task, a Rorschachlike perception problem, and a word association test. Siipola (1950) and Siipola, Kuns, and Tay-lor (1950) (1946, pp. 44, SS) indicate that stimulus words associated with longer response times tend to elicit comparatively more response words than stimulus words associated with relatively quick reaction times.…”
mentioning
confidence: 99%
“…Spontaneous changes in characteristics of responses within one Rorschach examination are discussed by Beck (9). In a study of changes in responses to a modified Rorschach test, Siipola et al (196) found that almost half the responses were changed more or less. Allen et al (2) report that two-thirds of the responses were changed.…”
Section: Studies Of Spontaneous (Aperiodic) Variabilitymentioning
confidence: 99%